Pengaruh Profesionalisme Guru dan Kecerdasan Emosional Terhadap Kinerja Guru Pendidikan Agama Islam di MTS Negeri 2 Bulukumba - Syahrum Syahrum; Syahruddin Usman; Nur Yamin (Manajemen Pendidikan, 2019)
The purpose of this study is to analyze the influence of teacher professionalism and emotional quotient to teachers’ performance of Islamic religious education at Islamic Junior High School 2 Bulukumba. This research is a field research by using quantitative approach through the ex post facto method. The participants of this research are 120 students from 604 students, taken through proportional random. Data collection technique with questionnaires and then analyzed by using regression analysis to examine the hypothesis. The results of this study show that partially, the teachers’ professionalism has a positive and significant effect on teachers’ performance of Islamic religious education, as well as the emotional quotient has a positive and significant effect on teachers’ performance of Islamic religious education. Simultaneously, teachers’ professionalism and emotional quotient has a positif and significant effect on teachers’ performance of Islamic religious education Thus, teachers’ professionalism and emotional quotient are the factors that determine the level teachers’ performance of Islamic religious education at Islamic Junior High School 2 Bulukumba.